Shaw potassium channel genes in Drosophila. - Hodge, J.J.L.; Choi, J.C.; O'Kane, C.J.; Griffith, L.C. (Journal of Neurobiology, 2005)
Drosophila Shaw encodes a voltage-insensitive, slowly activating, noninactivating K(+) current. The functional and developmental roles of this channel are unknown. In this study, we use a dominant transgenic strategy to investigate Shaw function and describe a second member of the Shaw family, Shawl. In situ hybridization showed that the two Shaw family genes, Shaw and Shawl, have largely nonoverlapping expression patterns in embryos. Shaw is expressed mainly in excitable cells of the CNS and PNS of late embryos. Shawl is expressed in many nonexcitable cell types: ubiquitously in embryos until the germband extends, then transiently in the developing CNS and PNS, becoming restricted to progressively smaller subsets of the CNS. Ectopic full-length and truncated Shaw localize differently within neurons, and produce uneclosed small pupae and adults with unfurled wings and softened cuticle. This phenotype was mapped to the crustacean cardioactive peptide (CCAP)-neuropeptide circuit. Widespread expression of Shaw in the nervous system results in a reduction in body mass, ether-induced shaking, and lethality. Expression of full-length Shaw had more extreme phenotypic consequences and caused earlier lethality than expression of truncated Shaw in a given GAL4 pattern. Whole cell recordings from ventral ganglion motor neurons expressing the truncated Shaw protein suggest that a major role of Shaw channels in these cells is to contribute to the resting potential.